Pluralization in Barman Thar: An Endangered Language - Primly Baruah, (Indian Journal of Social Science and Literature (IJSSL), 2025)
This paper examines the process of pluralisation in Barman Thar, an endangered language of Assam. This study aims to investigate the morphological and syntactic mechanisms involved in marking plurality in Barman Thar. The data collected for this paper are based solely on primary data gathered through fieldwork in Khoirabari and Tangla, located in Udalguri and Baksa districts of Assam. Singulars are unmarked in Barman Thar, and plurals are marked by suffixes like -taŋ and -phara, both of which are lexically and morphologically conditioned. Other syntactic categories, like numerals and reduplications, are also involved in forming plurality. Tibeto-Burman features, such as copula-drop and the lack of subject-verb agreement, can also be observed here. This paper not only attempts to investigate the Pluralisation process in Barman Thar but also supports the effort to revitalise this endangered language by documenting morphosyntactic patterns.